Analisis Aksesibilitas Evakuasi Tsunami Menggunakan Tools Network Analys Di Daerah Rawan Tsunami Kabupaten Tanggamus, Provinsi Lampung - Henky Mayaguezz; Moh. Muhaemin; Muhamad Gilang Arindra Putra (Universitas Bangka Belitung, 2023)
Geological activity in the areas around the Sunda Strait has received attention through the tsunami that occurred at the end of 2018. Other activity was also recorded through a tectonic earthquake in the Sunda Strait subduction zone with Magnitude 6.9 on 2 August 2019. This condition raises concerns about the threat of an earthquake and tsunami disaster in surrounding area. Tanggamus Regency, which is located around the Sunda Strait, has a very wide tsunami-prone lowland, especially in the area at the tip of Semangka Bay. Based on these conditions, this study generally aims to map tsunami-prone areas, evacuation service areas for each Temporary Evacuation Place (TES), and analyze evacuation accessibility models. To answer these challenges, this research was conducted using Geographic Information systems (GIS) by following several methodological steps. Starting from determining the study area using spatial analysis, determining TES points, digitizing the road network and integrating it with Network Analysis tools on the ArcGIS platform, determining evacuation service areas, and modeling the travel time from each population residents to the nearest TES. Based on the results, it was found that some of the farthest areas were Semaka District, Wonosobo District and Kota Agung Barat District. The sub-district has a higher travel time to reach TES than the estimated arrival time of the tsunami.